Piezoceramic sensor-based methods for RC structural health monitoring: A comparative study - Ziqian Yang; Minghui Zhang; Qingzhao Kong (Structural Health Monitoring, 2026)
Structural health monitoring (SHM) of reinforced concrete structures has attracted considerable attention over the past decades. Among various approaches, piezoceramic sensor-enabled active-sensing technique has proven effective for monitoring local damage, as it relies on the propagation of probing waves within a localized region of the host structures and extraction of damage-related information through advanced algorithms. To date, several classical methods for extracting damage information, including wavelet packet energy-based damage index, ultrasonic pulse velocity, diffuse ultrasonic coefficient, and coda wave interferometry, have been widely used for assessing concrete crack development. The performance of each method may vary under different cracking conditions; therefore, their effectiveness and reliability must be systematically evaluated. The present study provides a comprehensive comparison of representative piezoceramic sensor-enabled SHM methods via an experimental study, with the aim of providing a reference framework for beginners entering this research area and practical applications.